Analysis of Seabed Ecosystem Zonation Using Remote Sensing to Support Conservation Strategies on Ketawai Island, Central Bangka: Analisis Zonasi Ekosistem Dasar Laut Berbasis Penginderaan Jauh untuk Mendukung Strategi Konservasi di Pulau Ketawai, Bangka Tengah - Fifin Fitriana; Eka Altiarika (Journal of Global Sustainable Agriculture, 2025)
Seabed ecosystems such as coral reefs and seagrass beds play a vital role in maintaining ecological balance and supporting the livelihoods of coastal communities. Ketawai Island, located in Central Bangka, harbors rich benthic ecosystems that are currently under pressure from anthropogenic activities such as tin mining, unregulated tourism, and pollution. This study aims to analyze the condition of seabed habitats around Ketawai Island and to develop a conservation zoning framework using a spatial approach. The data used includes Sentinel-2A satellite imagery and 140 sample points analyzed using the Support Vector Machine (SVM) algorithm. The classification resulted in four substrate classes: rubble/dead coral (39.06%), live coral reefs (34.95%), sand (24.68%), and seagrass (1.31%), with a classification accuracy of 85%, validated using a confusion matrix based on 140 reference points, divided into 70% for training and 30% for validation. The conservation zoning was divided into four categories: core zone (providing full protection for healthy coral and seagrass habitats), rehabilitation zone (for ecosystem restoration), limited-use zone (for educational tourism and research under strict regulation), and buffer zone (as a transitional area to mitigate external pressure and support the sustainability of other zones). This study recommends the protection of remaining coral reefs and seagrass areas, along with restoration efforts in degraded regions. The proposed zoning provides a scientific basis for sustainable coastal management and serves as a strategic approach for adapting to climate change.